Padrões de herbivoria e efeitos na sobrevivência de plantas lenhosas jovens em uma Savana Neotropical - Raupp, Paola Pisetta (2021)
Leaves often show damage caused by insect herbivores in terrestrial ecosystems. During the first year of plants’ development, herbivory is considered the main biotic stressor responsible for reducing their survival. In this sense, herbivores can modify the abundance and distribution of plant species and, consequently, shape the structure of terrestrial communities. Understanding the functioning and role of herbivory during the early stages of plants life is the baseline to develop conservation strategies, which is particularly important for the Brazilian savanna, considered the richest tropical savanna in biodiversity of the world. In the first chapter of this thesis, we characterized and compared herbivory according to the frequency and leaf damage levels of woody saplings accounted for six insect guilds (mining, galling, sucking, rasping, chewing, and cutting) in two savanna formations (open and closed). We found that the frequency of herbivory on leaves varied according to vegetation formation and herbivore guild, being higher for cutting in closed savanna and for rasping and chewing in open savanna. Leaves of woody saplings in closed savanna showed a 1.4 times higher leaf herbivory level than open savanna, mainly due to cutting guild. This guild exhibited the highest level of leaf damage (~ 95%), including the removal of the shoot-system of plants through a cut in the hypocotyl made by leaf-cutter ants, which was never counted before. In our second chapter, we evaluated the survival and regrowth capacity of 1520 seedlings of 10 tree species with different seed sizes after simulating four levels of experimental herbivory of leaf-chewing insects (0%, 50%, 100%, and 100% plus hypocotyl) in open and closed savanna formation. We found that the survival of seedlings varied according to species, environment, and herbivory intensity. Defoliation up to 50% did not affect seedling survival in any savanna formation. Alternatively, high levels of herbivory (100% and 100% more hypocotyl) reduced seedling survival. Seedlings in open savanna had lower survival for all herbivory levels. In addition, intrinsic traits of plants such as seed size and growth capacity were positively related to successful plant establishment. Overall, our results found in both studies reinforce the role of herbivores insects in shaping plant communities. Finally, they provide important information for the development of restoration and conservation strategies for the Brazilian savanna, especially in places with the dominance of leaf-cutter ants.